THE CORRELATION BETWEEN THE IMPLEMENTATION OF DISCHARGE PLANNING AND THE LEVEL OF INDEPENDENCE OF INPATIENTS AT THE GENERAL REGIONAL HOSPITAL OF JEND. AHMAD YANI METRO - Hazizah, Siti Nur; Yunina Elasari; Moh. Heri Kurniawan; Rizki Yeni Wulandari (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
background: Discharge planning is a continuous nursing activity that starts from the time the patient enters the hospital until after discharge. Proper implementation of discharge planning is very important to increase patient independence in performingdaily activities (ADL). However, some studies say that many patients in several hospitals do not get adequate health education so that it has an impact on the level of patient independence after discharge from the hospital. Objective: The purpose of this study was to determine the correlation between the implementation of discharge planning and the level of independence of hospitalized patients at Jend. Ahmad Yani Metro Hospital . Method: This type of research uses quantitative research with a correlation research design with a cross-sectional approach. The population in this study were inpatients at Jend. Ahmad Yani Metro Hospital as many as 726 elderly respondents, with a sample of 97 elderly respondents. The sampling technique used probability with the proportionate stratified random sampling method. This study uses the Gamma statistical test. This research was conducted on September 17-26, 2024. Results: Based on the results of the study, there is a correlation between the implementation of discharge planning and the level of independence of hospitalized patients at the General Regional Hospital Jend Ahmad Yani Metro shows a p-value = 0.001 <0.05. Conclusion: This study provides information and input to hospitals regarding the importance of implementing structured discharge planning, starting from the assessment when the patient is admitted to the discharge evaluation. Nurses are expected to assess the environmental factors of patients, especially the elderly, to modify home environmental conditions that support their independence and at the preparation stage before the patient's discharge day by providing health education using leaflet media is very important to help elderly patients understand self-care at home and increase their independence after discharge.